PEMIKIRAN GENDER QURAISH SHIHAB DALAM TAFSIR AL-MISHBAH - Syarifatun Nafsi (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2016)
Abstract: Opinions Of Quraish Shihab On Gender In The Book Of Tafsir Al-Mishbah. Gender has become a hot topic now a day among the academicians. Equality of men and women always echoed both in the domestic sphere, as well as in international community. Qur’an as the main guidelines of Muslims who upholds justice, equality and opportunities for work for both men and women. But some times there misconception among the contra people and scapegoated Qur’an as the cause of their unequality in the community, especially the Muslim community. This at least from the perspective of feminist non-Muslims. Therefore, this paper describes the thinking of Quraish Shihab - as one of the commentators in Indonesia - which insists that Islam upholds the principles of justice, and condemned the arbitrary behavior toward women. This paper also discusses how Quraish Shihab interpret gender equality through the interpretation of the verses relating to the creation of male and female and male headship in the family. As a result, Quraish Shihab tend not to equate and fully align between men and women. Although similar and equally in his capacity as a human being and a servant of God and in the social life of the community, but in the role and function do not have to match exactly. Differences in the roles and functions of this is a relationship that is functionally complementary to each other as equal partners, so as to create a system and relationship harmony towards piety together.